2008
DOI: 10.1109/icact.2008.4493960
|View full text |Cite
|
Sign up to set email alerts
|

Securing U-Healthcare Sensor Networks using Public Key Based Scheme

Abstract:  Recent emergence of electronic culture uplifts healthcare facilities to a new era with the aid of wireless sensor network (WSN) technology. Due to the sensitiveness of medical data, austere privacy and security are inevitable for all parts of healthcare systems. However, the constantly evolving nature and constrained resources of sensors in WSN inflict unavailability of a lucid line of defense to ensure perfect security. In order to provide holistic security, protections must be incorporated in every compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…While the performance comparison has shown that our Table 3. Performance comparison between proposed scheme against schemes in [13] and [15]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the performance comparison has shown that our Table 3. Performance comparison between proposed scheme against schemes in [13] and [15]. …”
Section: Resultsmentioning
confidence: 99%
“…They applied symmetric encryption and RSA algorithm to complete the encryption and authentication for PHI. Hasque et al [15] proposed a secure u-healthcare sensor networks using public key based scheme. In their scheme, they adopted asymmetric encryption for confidentiality protection.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we obtain 12 12 1 3 31 31 21 21 2 3 32 32 3 12 12 21 21 Then, we obtain k and w . If 0 k  , 0 kl w , then 8 q is a stable point. This shows that the network system is stable, and the cooperative effect on the partner network is bigger than the competitive effect on the partner network or that the competitive effect is so small that it cannot induce the coalition system fluctuation.…”
Section: Analysis Of the Cooperative And Competitive Effectmentioning
confidence: 99%
“…In this section, we introduce various MSN-adaptive solutions since existing security mechanisms adopted in traditional networks such as wireless sensor networks [6][7][8] cannot be directly used in MSNs owing to characteristics of bio-sensors. Some solution for bio-data integrity and freshness exploit biometric information [9][10][11][12] and a symmetric key [13][14][15] or a public key [16,17].…”
Section: Previous Workmentioning
confidence: 99%